Spatiotemporal Analysis of Breast Cancer Hospitalizations in Portugal in 20022016 - Gomes,Inês Afonso (2020)
Introduction: Breast cancer (BC) is the most common cancer among Portuguese women and it is associated with high hospitalization rates. Therefore, this study aims to characterize the BC hospital admission rate (HAR) in women in the period of 20022016, with an additional focus on spatiotemporal patterns of hospitalizations by BC (main code). - Methods: After a descriptive analysis of all BC hospitalizations, the main BC code HAR was studied using mapping techniques, analysis of spatiotemporal clusters, and analysis of spatial variations in temporal trends. - Results: The BC-HAR was 118.72/10(5) women, showing a growth of 3.109% per year in this period. The median length of stay (LOS) in these patients was 5 days, and most cases were programmed surgical admissions. Several spatiotemporal clusters and spatial variations in temporal trends were detected. The seaside area of the country showed 4 high HAR clusters in the spatiotemporal analysis. Additionally, the seaside north of the country and 2 isolated counties presented significantly different temporal trends in BC-HAR versus the rest of the country. These clusters suggest regional asymmetries, as they showed differences in terms of: demographic characteristics (age at admission and rurality of county of residence), the type of admission, LOS, and outcomes of hospitalization. - Conclusion: This study identified key areas of high BC-HAR and increasing trends for female HAR, providing evidence of spatial heterogeneities in this health indicator.